2015
DOI: 10.1016/j.neuron.2015.06.033
|View full text |Cite
|
Sign up to set email alerts
|

How Can Single Sensory Neurons Predict Behavior?

Abstract: Summary Single sensory neurons can be surprisingly predictive of behavior in discrimination tasks. We propose this is possible because sensory information extracted from neural populations is severely restricted, either by near-optimal decoding of a population with information-limiting correlations or suboptimal decoding that is blind to correlations. These have different consequences for choice correlations, the correlations between neural responses and behavioral choices. In the vestibular and cerebellar nuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
236
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 136 publications
(250 citation statements)
references
References 40 publications
14
236
0
Order By: Relevance
“…When correlated noise is present, as is the case in the VN/CN (13,35), population thresholds may not decrease with the square root of the number of neurons and predictions based on the square root law could be dramatically inaccurate. Moreover, for a fixed neural pool size, population thresholds can also depend substantially on whether the decoder has full knowledge of the structure of noise correlations or not (42,45,46). Some noise correlations can be removed by an optimal decoder, but there is no guarantee that the brain is optimal and accounts for all correlations that can be removed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When correlated noise is present, as is the case in the VN/CN (13,35), population thresholds may not decrease with the square root of the number of neurons and predictions based on the square root law could be dramatically inaccurate. Moreover, for a fixed neural pool size, population thresholds can also depend substantially on whether the decoder has full knowledge of the structure of noise correlations or not (42,45,46). Some noise correlations can be removed by an optimal decoder, but there is no guarantee that the brain is optimal and accounts for all correlations that can be removed.…”
Section: Discussionmentioning
confidence: 99%
“…These contemporary theoretical studies have important implications for our findings. Specifically, the fact that some sensory fibers are nearly as sensitive as behavior would imply either information-limiting correlations or massively suboptimal decoding to account for behavior (42,45,46). We consider it more likely that the total information encoded by the otolith afferent population is constrained by information-limiting correlations (40), in which case it is inappropriate to use the square root law to predict behavioral thresholds as previous studies have done (26,37).…”
Section: Discussionmentioning
confidence: 99%
“…9). Also a recently developed formalism of relating choice probabilities to stimulus preferences gives support to the scenario of saturated information and optimal readout as opposed to nonsaturated information and suboptimal readout (59). The above arguments address the case of computationally simple tasks like orientation discrimination; for hard tasks like object recognition under naturalistic viewing conditions the readout of V1 is likely suboptimal due to extensive computational approximations of downstream circuitry (60).…”
Section: Computation-induced Noise Correlations Contain a Tiny Amount Ofmentioning
confidence: 99%
“…Although we have previously shown that the activity of disparity-selective neurons in V2 is correlated with a macaque monkey's perceptual decision in a "coarse" dis-parity discrimination task (Fig. 1B) (Nienborg and Cumming, 2006, no one has examined this correlation for "fine" tasks that depend on relative disparity (Fig. 1A).…”
Section: Introductionmentioning
confidence: 97%
“…The first stage in the primate cortex that contains a subgroup of neurons selective for relative disparity is visual area V2 (Thomas et al, 2002;Neri et al, 2004). Although we have previously shown that the activity of disparity-selective neurons in V2 is correlated with a macaque monkey's perceptual decision in a "coarse" dis-parity discrimination task (Fig.…”
Section: Introductionmentioning
confidence: 99%